Ceramide signalling impinges on Sit4p and Hog1p to promote mitochondrial fission and mitophagy in Isc1p-deficient cells - Teixeira, Vitor (2015)
Mitochondria function as the powerhouses of the cell for energy conversion through the oxidative phosphorylation process. Accumulation of dysfunctional mitochondria promotes a bioenergetic crisis and cell death by apoptosis. Yeast cells lacking Isc1p, an orthologue of mammalian neutral sphingomyelinase type 2, exhibit mitochondrial dysfunction and shortened lifespan associated with the accumulation of specific ceramide species and activation of the PP2A-like protein phosphatase Sit4p and of the Hog1p kinase. Here, we show that isc1δ cells display hyperactivation of mitophagy that is suppressed by downregulating Sit4p, Hog1p or the TORC1-Sch9p pathway. Notably, isc1δ cells also have high levels of Dnm1p associated with unbalanced mitochondrial fission, leading to mitochondrial fragmentation, and DNM1 deletion suppressed the oxidative stress sensitivity and shortened lifespan of isc1δ cells. Moreover, Isc1p and Dnm1p physically interact, suggesting a possible regulatory role for Isc1p in mitochondrial dynamics. Overall, our work demonstrates that Isc1p-mediated ceramide signalling regulates mitophagy and mitochondrial dynamics in yeast with impact on mitochondrial function and lifespan. Since ceramides have been implicated in ageing and diseases associated with mitochondrial dysfunction, our findings suggest that therapeutic strategies targeting ceramide signalling may improve mitochondrial function and human healthspan.